SPDC Conversion from Bound State in the Continuum in Semiconductor Metasurfaces: Polarization Properties - Gennaro, Sylvain D.; Santiago-Cruz, Tomás; Mitrofanov, Oleg; Vabishchevich, Polina P.; Addamane, Sadhvikas; Bethke, Don; Reno, John; Chekhova, Maria V.; Brener, Igal (Optics InfoBase Conference Papers, 2022)
We study the polarization properties of photon pairs emitted via spontaneous parametric down-conversion from a nonlinear metasurface driven by symmetry-protected, bound state in the continuum.
CRIS-Team Scopus Importer:2022-09-09